Evaluation of Dental Diseases of Pregnant Women in Tikrit Governorate in Iraq - Sulafa K. Banoosh (Journal of Global Pharma Technology, 2019)
Aim: is to find any relation between the dental diseases and pregnancy. Material and meathods: 100 pregnant ladies their age between (19-40) year’s old.33 pregnant ladies in the first trimester, 33 pregnant ladies in the second trimester, and 34 pregnant ladies in the third trimester. All healthy looking and were accepted to be in this study. Stimulated salivary samples collected according to special instructions. The pH estimated at the time of collection and the salivary flow rate was estimated by divided the volume of saliva in collecting tubes in milliliter per minutes (ml/min). Oral examination was done using plane mouth mirror and dental explorer. And all teeth was examined for caries lesions and recorded by (DMFt) index according to criteria depicted by oral health survey of world health organization (WHO). Plaque index for dental plaque thickness and calculus index was used also for recording the periodontal conditions. Results: The results of the current study revealed that the dental caries severity represented by DMFt index had significant differences in the third trimester than the other trimesters and negatively relative with the salivary pH in the third trimester during pregnancy the (p< 0.05). Conclusion: There were a relation between the dental caries severity and pregnancy this could be due to the fact that the anxious and restless and exhausted in addition to nausea and vomiting that make the routine oral hygiene practices more difficult.Keywords: Trimester, DMFt, WHO, Plaque index, PH.